2020
DOI: 10.1371/journal.pgen.1009215
|View full text |Cite
|
Sign up to set email alerts
|

Bud23 promotes the final disassembly of the small subunit Processome in Saccharomyces cerevisiae

Abstract: The first metastable assembly intermediate of the eukaryotic ribosomal small subunit (SSU) is the SSU Processome, a large complex of RNA and protein factors that is thought to represent an early checkpoint in the assembly pathway. Transition of the SSU Processome towards continued maturation requires the removal of the U3 snoRNA and biogenesis factors as well as ribosomal RNA processing. While the factors that drive these events are largely known, how they do so is not. The methyltransferase Bud23 has a role d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 92 publications
1
35
0
Order By: Relevance
“…Indeed, ectopic expression of RPS2 partially restored growth in the bud23∆ cells (Figure 2A). Our previous analyses of extragenic suppressors of bud23∆ showed that these suppressors partially alleviate the 40S biogenesis defect of bud23∆ cells (Sardana et al 2013;Black et al 2020). To assess whether the partial suppression of bud23∆ due to ectopic RPS2 also improved 40S production, we analyzed ribosome subunit levels by separating extracts on sucrose density gradients.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, ectopic expression of RPS2 partially restored growth in the bud23∆ cells (Figure 2A). Our previous analyses of extragenic suppressors of bud23∆ showed that these suppressors partially alleviate the 40S biogenesis defect of bud23∆ cells (Sardana et al 2013;Black et al 2020). To assess whether the partial suppression of bud23∆ due to ectopic RPS2 also improved 40S production, we analyzed ribosome subunit levels by separating extracts on sucrose density gradients.…”
Section: Resultsmentioning
confidence: 99%
“…Bud23 is a conserved methyltransferase that modifies G1575 of 18S rRNA in yeast (G1539 in humans) during 40S biogenesis (White et al 2008;Figaro et al 2012;Létoquart et al 2014;Zorbas et al 2015). We previously proposed that Bud23 binds to a partially disassembled Processome where it coordinates the activities of the GTPase Bms1 and the RNA helicase Dhr1 to ensure the productive folding of the central pseudoknot (CPK) as the nascent particle transitions into the pre-40S (Black et al 2020;Black and Johnson 2021). Consistent with the role of Bud23 in CPK formation, we found here that the overexpression of Rps2, which binds to the CPK, partially bypassed the defects caused by bud23∆ (Figures 2A & 2B).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations